DATA SCIENTIST CERTIFICATION GUIDANCE FOR SENIOR HIGH SCHOOL AND UNIVERSITY STUDENTS - Triana, Yaya Sudarya; Budiarto, Rahmat; Rahmad, Khozaeni Bin (Jurnal Pengabdian Masyarakat Nasional, 2025)
The importance of using Information and Communication Technology can increase our role in the Modern Era among academics, which is one of the driving factors to be able to compete in the digital world. The use of technology is not only for social media, but the use of technology has an important role in the world of work today. The increasingly rapid development of technology has created many changes and updates in every field. One of the applications most widely used and needed by society is Data Science. Data Science is a multi-disciplinary science that is very widely used in both exact and social fields. To make your job search easier, Data Scientist certification is required. This of course requires someone who is competent in their field. Today's young generations should be worthy of having these competencies. Based on the above, the lecturers at the Faculty of Computer Science, Universitas Mercu Buana contributed to providing a coaching understanding in the application of Information and Communication Technology to increase knowledge in the Modern Era among academics so that they can equip the younger generation to have certification in the field of information technology, especially Data Scientists. This activity or training is a form of concern and is also one of the duties as a lecturer at the Faculty of Computer Science who understands information technology, especially in the field of Data Science.